Validity and reliability of the Cortex MetaMax3B portable metabolic system - Vogler, A. J.; Rice, A. J.; Gore, C. J. (Journal of Sports Sciences, 2010)
Portable indirect calorimetry systems offer the advantage of field-based measurements, but manufacturers rarely provide data about validity or reliability. In this study, we evaluated the validity and reliability of the Cortex MetaMax3B portable metabolic system. Validity was determined by comparing MetaMax3B results against those from a first-principles metabolic calibrator and an automated Douglas bag system. Reliability was obtained from duplicate exercise tests completed by eight athletes. Participants completed three identical incremental rowing tests on a Concept2 ergometer; two tests used the MetaMax3B and one test used the Douglas bag system. Compared with the metabolic calibrator, the MetaMax3B results were within 0.20 litres/min (7.8%) and 6.15 litres/min (4.0%) for [V]O2 and VE, respectively. During exercise, the MetaMax3B results were within 0.16 litres/min (4.1%; [V]O2), 0.32 litres/min (7.7%; [V]CO2), and 3.22 litres/min (4.9%; VE) compared with the Douglas bag system. The MetaMax3B results were significantly higher for [V]O2 (P = 0.03) and [V]CO2 (P < 0.001). The typical error from duplicate exercise tests using the MetaMax3B ranged from 2.0% ([V]O2) to 3.6% (VE). Our results show that the MetaMax3B provides reliable measurements of metabolic demand with adequate validity for field-based measurements.